2010
DOI: 10.1007/s00380-009-1159-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CYBA, PPARGC1A, PPARG3, and PPARD gene variants with coronary artery disease and metabolic risk factors of coronary atherosclerosis in a Russian population

Abstract: Abnormalities in lipid metabolism and enhanced oxidative stress are considered as major risk factors for coronary atherosclerosis. Functional genetic variations in genes whose products are involved in lipid metabolism and antioxidant defense could therefore modulate risk of coronary artery disease (CAD). In this study, we evaluate whether the PPARGC1A Gly482Ser, PPARG3 (-681)C/G, PPARD +294T/C, and CYBA +242C/T gene variants confer the risk of CAD in a Russian population. A total of 313 CAD patients and 132 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
45
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 49 publications
1
45
0
2
Order By: Relevance
“…PPARD rs2016520 showed no association with CHD, but was significantly associated with cholesterol metabolism in a Scottish study (Skogsberg et al, 2003). The PPARD rs2016520 polymorphism was associated with serum lipid levels and the risk of CHD in Russians (Nikitin et al, 2010). PPARD rs2016520 increased the effect of low-density lipoprotein-cholesterol on the pathogenesis of CHD in a Turkish population (Yilmaz-Aydogan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PPARD rs2016520 showed no association with CHD, but was significantly associated with cholesterol metabolism in a Scottish study (Skogsberg et al, 2003). The PPARD rs2016520 polymorphism was associated with serum lipid levels and the risk of CHD in Russians (Nikitin et al, 2010). PPARD rs2016520 increased the effect of low-density lipoprotein-cholesterol on the pathogenesis of CHD in a Turkish population (Yilmaz-Aydogan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A number of case-control studies have indicated that PPARD rs2016520 is associated with CHD. A previous study in Russians found a significant association between the PPARD rs2016520 polymorphism and the risk of CHD by modulating lipid levels (Nikitin et al, 2010). A study performed in Tunisians indicated that the minor allele of PPARD rs2016520 was associated with CHD (Jguirim-Souissi et al, 2010;Chehaibi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 PPAR-B/D geni 5'-UTR bölgesinde tanımlanan +294T/C tek nükleotit polimorfizmi (SNP) (rs52016520) minör C alleli ile yüksek LDL kolesterol (LDL-K) ve apoB düzeyleri, vücut kitlesi ve düşük HDL kolesterol (HDL-K) düzeyleri ilişkili olarak aterojenik etkili bulunmuştur. 13,[29][30][31][32][33] Ancak bazı çalışma sonuçları çelişkilidir. [34][35][36] PPAR-B/D +294T/C minör C allelinin yüksek HDL-K düzey-leri ile ilişkili olduğunu ya da serum lipid düzeyle-rine etkisiz olduğunu öne süren çalışmalar da mevcuttur.…”
unclassified